The Security Implication of China’s Unlimited Presidential Term on Africa - Okafor, Frank-Collins; Mark, Kingsley (Journal of Public Policy and Administration, 2023)
Purpose: This paper looks at the security implication of China's policy of unlimited presidential term on Africa, noting that "He that pays the piper determines it pace" as such; Africa being at the receiving end of Chinese aid, goods, services, military supplies and assistance and Chinese military presence in some African countries notwithstanding will continue to depend on the whims and caprices of China. Methodology: Using Marxist Economic Theory of Imperialism and Dependency theory, the paper argues that the policy will continue to take advantage of the systemic and structural imbalance of the African economic, political and strategic/military architecture. As such her dependent on China, which in the long-run engenders neo-colonial condition favourable to China's strategic interest in Africa. Findings: The all-pervading Chinese presence in Africa visa-vise her policy of unlimited presidential term serves as instrument of imperialism to Africa, parasitically corroding strategic, national economic base and provokes acute neo-colonialism which at the stance of dependency state. Hence the dire need for a wakeup call to countries of African to develop and incorporate advance security measures to avoid the risk of continual domination of Africa strategic and economic relation by China, which has continued to engenders communal crisis and inter-tribal wars orchestrated by her regular arms sale to African countries, as one will agree that term limit in governance is one of the few checks on the ruler embedded in the state constitution that can quickly bring about a change in government policy and philosophy. Unique Contribution to Theory, Practice and Policy: This paper recommends among others, that African countries should carry their destiny in their own hands instead of succumbing to the prevailing China's national interest (aid) driven interventions which is currently re-championed in her current unlimited presidential term.